Collaborative Governance dalam Pengelolaan Taman Harmoni Keputih di Kota Surabaya - Rafael Putra Dinata; Yusuf Hariyoko; Wahid Hidayat (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
The rapid pace of urbanization in Indonesia demands a more collaborative approach to the management of Urban Green Open Spaces (GOS). Responding to this challenge, this study examines the implementation of collaborative governance at Taman Harmoni Keputih, Surabaya, by adopting the integrative framework proposed by Emerson, Nabatchi, & Balogh (2012). Employing a descriptive qualitative method, data were collected through interviews, observation, and documentation studies conducted from April to June 2026. Field findings indicate that the synergy established among the Environmental Agency (DLH), Transportation Agency, Keputih Sub-district Office, Joint Business Group (KUBE), and private sector has been functioning effectively. This partnership has proven capable of optimizing park maintenance, stimulating the local economy, and fostering a sense of ownership among residents. Nevertheless, community and KUBE participation remains limited to the implementation phase. Furthermore, cross-sector coordination is still confined to the technical-operational level, accompanied by an adaptive pattern toward field constraints that tends to be situational. Therefore, this study recommends strengthening public involvement in decision-making processes, developing accountable standard operating procedures (SOPs), and enhancing KUBE's institutional capacity to create a more inclusive and sustainable governance framework